Islamophobia – The Experience in Worlds Old and New: Lessons from Europe and Australia (American Journal of Islam and Society, 2009)
Organized jointly by the Australian Intercultural Society, the AustralianCatholic University, and Monash University together with the Gülen conferencea few days earlier, this conference was devoted to a particularly important and pressing topic: the anti-Islam discourse slowly becoming a standardfeature of western political competition and media coverage. As the topic issimilarly a rather polarizing one, an event of high scholarly quality could notbe taken for granted. However, this is just what organizers, speakers, andaudience managed to achieve during this event, held during 18-19 July 2009at Monash University in Melbourne. The phenomena subsumed under theterm Islamophobia, their expressions, preconditions, and multiple roots andfacets were discussed through different approaches in theoretical, descriptive,and analytical terms ...